Africa and the disruptions of the twenty-first century - Zeleza, Paul Tiyambe, 1955- (Codesria book series., 2021)
This collection of essays interrogates the repositioning of Africa and its diasporas in the unfolding disruptive transformations of the early twenty-first century. It is divided into five parts focusing on America's racial dysfunctions, navigating global turbulence, Africa's political dramas, the continent's persistent mythologisation and disruptions in higher education. It closes with tributes to two towering African public intellectuals, Ali Mazrui and Thandika Mkandawire, who have since joined the ancestors.